2020
DOI: 10.1186/s12966-020-00935-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations with physiological, psychosocial and educational outcomes of meeting Australian 24-Hour Movement Guidelines for the Early Years

Abstract: Background: Several countries have released movement guidelines for children under 5 that incorporate guidelines for sleep, physical activity and sedentary behavior. This study examines prospective associations of preschool children's compliance with the 24-Hour Australian movement guidelines (sleep, physical activity, screen time) and physiological, psychosocial and educational outcomes during primary school. Methods: Data were from the Healthy Active Preschool and Primary Years Study (Melbourne, Australia; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 61 publications
6
69
1
Order By: Relevance
“…Older children’s sleep may have increased from a lack of formal school start times, akin to delaying school start times [ 30 ], which is not as rigid in preschools. This imbalance of movement behaviors is particularly concerning given evidence that preschoolers who do not meet movement guidelines over the long-term experience negative consequences of higher adiposity [ 42 ], lower educational outcomes [ 5 ], and compromised physiological development [ 5 ], and the COVID-19 outbreak is creating a long-term challenge to household routines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older children’s sleep may have increased from a lack of formal school start times, akin to delaying school start times [ 30 ], which is not as rigid in preschools. This imbalance of movement behaviors is particularly concerning given evidence that preschoolers who do not meet movement guidelines over the long-term experience negative consequences of higher adiposity [ 42 ], lower educational outcomes [ 5 ], and compromised physiological development [ 5 ], and the COVID-19 outbreak is creating a long-term challenge to household routines.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate balance of movement behaviors, including physical activity, screen-time, and sleep, is important for child physical and mental development [ 1 3 ]. An imbalance of movement behaviors, characterized by low levels of physical activity and sleep and high levels of screen-time, may hinder cognitive development [ 4 , 5 ] and promote childhood obesity [ 6 , 7 ]. The World Health Organization (WHO) recently recognized the importance of movement behaviors by creating the 24-h movement guidelines for children [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a multinational, observational study of children aged 9-11 years, children had significantly higher HRQOL when they met the screen time recommendation only, the screen plus sleep recommendations, and all three recommendations compared with those who met none [30]. Another study followed children aged 3-5 until they were aged 9-11 years and found no significant associations between baseline 24-h movement behaviors (capturing physical activity, screen use and sleep) and later HRQOL among 471 children [31]. The two studies had either a narrow age range or a relatively small sample with the majority of the participants from urban or relatively high socioeconomic background families.…”
Section: Plain English Summarymentioning
confidence: 98%
“…Several studies have investigated the relationship between HRQOL and physical activity, screen use, and sleep separately [5,9,27] or a combination of two of them in selected age groups of children [28,29]. To the best of our knowledge, only two previous studies directly investigated the association between 24-h movement behaviors and HRQOL [30,31]. In a multinational, observational study of children aged 9-11 years, children had significantly higher HRQOL when they met the screen time recommendation only, the screen plus sleep recommendations, and all three recommendations compared with those who met none [30].…”
Section: Plain English Summarymentioning
confidence: 99%
“…Although Australian preschool children (aged 3- to 5-years) spend around 5–6 h per day being physically active [ 6 , 7 ], with the majority meeting the physical activity guidelines of 180 min/day [ 6 , 8 ], their physical activity is sporadic in nature [ 7 ]. In addition, they spend more than 50 % of their waking hours sedentary [ 7 ].…”
Section: Introductionmentioning
confidence: 99%